N-Acetyl cysteine for prevention of contrast induced nephropathy (University Heart Journal, 2010)
The antioxidant N-acetyl Cysteine prevents contrast induced nephropathy in patients with impaired renal function who undergo coronary angiogeaphy. However its role in Bangladeshi population is not clear. This study was done determine whether oral acetylcysteine prevents contrast induced nephropathy in high risk patients.100 patients with mild to moderate renal insufficiency who are undergoing elective coronary angiography with or without intervention.50 patients were randomy assigned to receive oral N acetyl cysteine (600mg) twice daily on the day before and on the day of procedure. All patients received low osmolar contrast agent.10 (20%) control patients (no premedicationgroup) and none of acetyl cysteine (0%) group developed a more than 25% increase in serum creatinine level within 48 hours after contrast exposure. Acetyl cysteine prevents contrast induced nephropathy. Keywords : Anti Oxidant; contrast induced nephropathy. DOI: 10.3329/uhj.v5i2.4554 University Heart Journal Vol.5(2) July 2009 pp.56-58